Editor's Note = Note du directeur [16, Fall 1985] - Kealey, Gregory S. (Labour / Le Travail, 1985)
Notes with great sadness the recent deaths of Marta Danylewycz, Leo Roback, and Herbert G. Gutman. The current volume is dedicated to their memory.
Keywords: DANYLEWYCZ; Marta; FEMINISTS; GUTMAN; Herbert George; 1928-1985; Historians; Journalists; ROBACK; Leo

Book Notes [15, Spring 1985] - Kealey, Gregory S.; C. de B. (Labour / Le Travail, 1985)
The article reviews "The Garden Transformed: Prince Edward Island, 1945-1980," by Verner Smitheram, David Milne, and Satadal Dasgupta, "Women and Trade Unions in Eleven Industrialized Countries," edited by Alice Cook, Val R. Lorwin, and Arlene Kaplan Daniels, "Black Socialist Preacher: The Teachings of Reverend George Washington Woodbey and his Disciple Reverend George W. Slater, Jr.," edited by Philip S. Foner, "Supremacy and Subordination of Labour: The Hierarchy of Work in the Early Labour Movement," by Mike Holbrook-Jones,"Canadian Papers in Rural History," v. 4, edited by Donald H. Akenson, "The Company on the Coast," edited by E. Blanche Norcross, "Class Power and State Power; Political Essays," by Ralph Miliband, "Labor in the World Social Structure," v. 2, edited by Immanuel Wallerstein, "The Polish Peasant in Europe and America," by William I. Thomas and Florian Znaniecki, edited and abridged by Eli Zaretsky, "Shopkeepers and Master Artisans in Nineteenth-Centurv Europe," edited by Geoffrey Crossick and Heinz-Gerhard Haupt, "Family Honour: An American Life," by George Cuomo, "Passages in the Life of a Radical," by Samuel Bamford, "In the Tracks of Historical Materialism," by Perry Anderson, "Marx and Engels: A Conceptual Concordance," by Gerard Bekerman, "Twenty Years of the Fishermen's Protective Union of Newfoundland," edited by Hon. Sir W.F. Coaker, / reviews by Gregory S. Kealey – "The Culture of Technology," by Arnold Pacey / review by C. de B.

Pre-industrial Canada, 1760-1849 - Cross, Michael S.; Kealey, Gregory S. (McClelland and Stewart, 1985)
...This volume presents a selection of scholarly articles designed to introduce the student to currents of social change and development in Canada from 1760 to 1849. With contributions by such respected academic writers as Harold Adams Innis, Judith Fingard, and Sylvia Van Kirk, it provides valuable insights into the role of the working class, violence and protest, class conflicts, and the economic structure of a newly developing nation. –Publisher's description
OCLC: 806289951
Keywords: 1800-1899; Canada; Canada Conditions sociales 19e siècle; Canada Conditions économiques 19e siècle; Canada Economic conditions 19th century; Canada Social conditions 19th century; Economic history; Social conditions

Lectures in Canadian Labour and Working-Class History - Cherwinski, W. J. C. (Walter Joseph Carl); Kealey, Gregory S.; Committee on Canadian Labour History (AU Press, 1985)
In 1983 and 1984 the Canadian Studies Program of the Secretary of State funded four lecture series at Canadian universities on the history of the Canadian working class. This volume presents many of the lectures in a published version. Ranging from east to west and covering two centuries of Canadian labour history, the volume includes a selection of essays by some of Canada's leading social historians including Michael Cross, David Frank, Ross McCormack, Bryan Palmer and Joy Parr. Outstanding participants in the making of Canadian labour history Eugene Forsey and H. Landon Ladd have also contributed. Directed at a popular audience these fourteen lectures provide a major survey of Canada's labour past. –Publisher's description
https://archive.org/details/lecturesincanadi0000unse http://www.aupress.ca/index.php/books/cclh01
Keywords: Canada; History; Labor; Labor Unions; Labor movement; Working class